Spol in slovenski poosamosvojitveni film - Poglajen, Tina (Družboslovne razprave, 2017)
The article investigates representations of sexual violence in cinema of the independent Slovenia, drawing on the psychoanalytic cinema apparatus theory of the spectatorial gaze, which is constituted as masculine and condones sexual violence. We believe the national institution for financing of film production, the Slovenian Film Fund (1994-2010), functions as a gatekeeper that indirectly influences the content of the films that are made, while cinema itself functions as an ideological state apparatus. Analysis of the film texts shows the ubiquitous motives of rape and sexual violence against women in the cinema of the independent Slovenia function as punishment for promiscuity or other ways of disrespecting the patriarchal order.
Keywords: Slovenian motion pictures; Slovenski film; Film criticism; Filmska kritika; Feminism; Feminizem; Sexual violence; Spolno nasilje; Slovenia; Slovenija; Filmski sklad Republike Slovenije; filmska produkcija